Minimally Invasive Transpedicular Dorsal Stabilization of the Thoracolumbar and Lumbar Spine Using the Minimal Access Non-Traumatic Insertion System (MANTIS): Preliminary Clinical Results in 52 Patients - Özkan, Neriman; Sandalcioglu, Ibrahim Erol; Petr, Ondra; Kurniawan, Anastasia; Dammann, Philipp; Schlamann, Marc; Sure, Ulrich; Asgari, Siamak (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background The aim of this study is to report about a preliminary experience with a new minimally invasive percutaneous transpedicular dorsal stabilization system (MANTIS, Stryker, Kalamazoo, MI, USA) for thoracolumbar and lumbar spinal diseases to demonstrate the benefits of the operative technique and drawbacks.Material and Methods The minimally invasive percutaneous transpedicular stabilization technique was performed in 52 patients with thoracolumbar and lumbar spinal diseases from February 2009 to August 2010. The average age of 25 male and 27 female patients was 60 years (range 15 to 81 years). Visual analog scale (VAS) was used for pre- and postoperative evaluation of pain. In all patients, preoperative magnetic resonance imaging and computed tomography (CT) scan were performed to evaluate the neuronal and bony structures. Screw position of all operated segments was controlled by postoperative CT scan.Results Indication for surgery was spondylolisthesis in 28 cases (53.8%), vertebral fracture in 15 cases (28.8%), vertebral metastasis in 8 patients (15.4%), and spondylodiscitis in 1 patient (1.9%). Decompressive laminectomy was performed in 37 cases (71.2%). An additional interbody fusion was necessary in 26 patients (50%) due to degenerative motion spondylolisthesis. All patients showed pain improvement after surgery. The average preoperative VAS score was 7.98 (minimum 5 and maximum 10) and improved after surgery to 2.15 (minimum 0 and maximum 8). The rate of screw misplacement was 4.62% (10 of 216 screws). We revised three screws (1.38%) in three different patients (5.6%) due to suboptimal screw position although these patients had no neurological deterioration. Postoperative complications include cerebrospinal fluid leakage in four cases (7.7%), which occurred during the decompressive procedure. One patient showed a postoperative hematoma located in the paravertebral muscle.Conclusion Minimally invasive transpedicular screw stabilization systems such as the MANTIS lead to safe and effective procedures. They can be used for different spinal disorders and can be combined with additional surgical procedures such as intervertebral fusion or decompression, if necessary.
Keywords: pedicle screws; minimally invasive surgery; lumbar spine; spondylolisthesis